Foreigner’s internal migration in Spain: recent spatial changes during the economic crisis - F. Gil-Alonso; Jordi Bayona Carrasco; Isabel Pujadas Rúbies (Boletín de la Asociación de Geógrafos Españoles, 2015)
Texto resumen.